Análisis del tereftalato de polietileno (plástico PET) en tuberías hidráulicas domésticas bajo diversos régimen de flujo (2020)
In this document a grade proposal is presented in order to modify the diagram of Moody implementing as a new use to bottles bottles made of polyethylene terephthalate (PET) in order to transform the material into raw material by converting it by means of necessary processes into drinking water pipes by adding its use to the domestic distribution networks. PET plastic containers are widely used in the areas of Barranquilla being scattered in the streets, dumps and gutters, creating contaminated environments. This material has similar characteristics Polyvinyl chloride (PVC), the use of such material in a recycled form is therefore desired while reducing the negative environmental impact by providing a new use as a hydraulic pipe in intrahousehold networks, being a positive approach for engineering, since it would be implementing new ways of obtaining construction materials, analysing the different factors that are generated within them, such as friction losses under different flow regimes, leading to the development of the Moody Diagram for this type of material according to the behavior presented by the fluid. Within the observations of the material transformed into a pipe, the water hammer calculation is carried out, which consists of showing the behavior of said pipe under pressure.